Sistem Informasi Monitoring Siswa Bermasalah Berbasis Web dan SMS Gateway (Studi Kasus : SMA Negeri 2 Trenggalek) - Prambudi, Fandi Setyo; Arifin, Mochammad; Nurcahyawati, Vivine (Jurnal JSIKA, 2012)
Students with problems requiring special attention on the problem, therefore Counseling (BK) on duty to brief the students to help solve existing problems. Limited number of tasks and supervising teacher be an obstacle in the process of monitoring troubled students. Similarly, parents who are still difficulties in monitoring the activities of their children in school.Certainty Factor is a clinical parameter values ​​are given to demonstrate the magnitude of the trust. Determination of troubled students is done by giving the value of CF (Certainty Factor) on three criteria: academic, and violations of the student profile that produces a combination of the CF as a conclusion about troubled students.Web-based application with the application of Certainty Factor is used as a means for monitoring the state of students as well as SMS Gateway technology is used as a media service of parents in monitoring their children in school activities. With this application, especially the school Counseling can monitor and obtain reports the troubled condition of students and facilitate parents to get information about the activities of their children in school. Keyword: Monitoring, Siswa bermasalah, Certainty Factor, SMS Gateway